In vitro and in silico evaluation of 5-MeO-DMT, LSD, and mescaline’s interaction with CYP450 enzymes - Machado Brito-da-Costa, Andreia; Carvalho, Mariana; Dinis-Oliveira, Ricardo Jorge; Madureira-Carvalho, Áurea; F. Sousa, Sérgio; Dias da Silva, Diana (Scientific Letters, 2024)
Background: 5-Methoxy-N,N-dimethyltryptamine (5-MeO-DMT), lysergic acid diethylamide (LSD), and mescaline are classic hallucinogens known for their recreational use, which increased in the last decades. Despite some available data on the metabolism of these drugs [1-3], a scientific gap exists regarding their possible interactions with CYP450 enzymes. Nevertheless, this information is of crucial relevance to predict drug-drug interactions and understand toxicological phenomena, in particular interindividual variability. Objective: This study aimed to evaluate in vitro and in silico the interaction of 5-MeO-DMT, LSD, and mescaline with the enzymes CYP2A6/2B6/2D6/2E1/3A4. Methods: The in vitro assessment of CYP450 inhibition was performed using the Vivid®CYP450 screening kits. IC50 was calculated using GraphPad Prism 9.3.0. For in silico assessment, molecular dynamics were performed using the PMEMD.cuda module in AMBER16. Calculations were made on the last 100 ns of the trajectory (stable zone) to assess the interaction mode/strength between enzyme and ligand, namely MMGBSA, per-residue decomposition energy, and hydrogen bonds.Results: Based on the IC50 (mM), LSD (0.35) and 5-MeO-DMT (3.47) present the capacity to be inhibitors of CYP2D6. Based on the MMGBSA (kcal/mol), LSD showed the highest binding affinities for all enzymes, while mescaline showed the lowest. The strong interaction of LSD with CYP2A6 is mediated by a hydrogen bond established with the protein residue Asn297. For interaction with CYP2B6, the residues Thr302 and Lys479 were important in mediating the interaction with 5-MeO-DMT and LSD. Key residues mediating the interaction of 5-MeO-DMT and LSD with CYP2D6 included Phe120, Leu213, and Phe483. For interaction with CYP2E1, residues Phe207, Phe298, and Thr303 are important; and for CYP3A4, an important hydrogen bond between LSD and Ala370 was identified. Conclusions: Both LSD and 5-MeO-DMT are predicted to have strong potential to be CYP2D6 inhibitors. A strong interaction was also identified in silico between LSD and CYP2A6.